Comparative analysis of prognostic histopathologic parameters in subtypes of epithelioid pleural mesothelioma. Issue 1 (25th May 2020) - Bilecz, Agnes; Stockhammer, Paul; Theegarten, Dirk; Kern, Izidor; Jakopovic, Marko; Samarzija, Miroslav; Klikovits, Thomas; Hoda, Mir A; Döme, Balázs; Oberndorfer, Felicitas; Muellauer, Leonhard; Fillinger, János; et al.
Abstract : Aims: Malignant pleural mesothelioma (MPM) is a rare malignancy with a dismal prognosis. While the epithelioid type is associated with a more favourable outcome, additional factors are needed to further stratify prognosis and to identify patients who can benefit from multimodal treatment. As epithelioid MPM shows remarkable morphological variability, the prognostic role of the five defined morphologies, the impact of the nuclear grading system and the mitosis‐necrosis score were investigated in this study. Methods and results: Tumour specimens of 192 patients with epithelioid MPM from five European centres were histologically subtyped. Nuclear grading and mitosis–necrosis score were determined and correlated with clinicopathological parameters and overall survival (OS). Digital slides of 55 independent cases from The Cancer Genome Atlas (TCGA) database were evaluated for external validation. Histological subtypes were collapsed into three groups based on their overlapping survival curves. The tubulopapillary/microcystic group had a significantly longer OS than the solid/trabecular group (732 days versus 397 days, P  = 0.0013). Pleomorphic tumours had the shortest OS (173 days). The solid/trabecular variants showed a significant association with high nuclear grade and mitosis–necrosis score. The mitosis–necrosis score was a robust and independent prognostic factor in our patient cohort. The prognostic significance of all three parameters was externally validated in the TCGA cohort. Patients with tubulopapillary or microcystic tumours showed a greater improvement in OS after receiving multimodal therapy than those with solid or trabecular tumours. Conclusions: Histological subtypes of epithelioid MPM have a prognostic impact, and might help to select patients for intensive multimodal treatment approaches.